Extensive multiregional urea elevations in a case-control study of vascular dementia point toward a novel shared mechanism of disease amongst the age-related dementias - Philbert, Sasha A.; Xu, Jingshu; Scholefield, Melissa; Patassini, Stefano; Church, Stephanie J.; Unwin, Richard D.; Roncaroli, Federico; Cooper, Garth J. S. (Frontiers in Molecular Neuroscience, 2023)
Introduction Vascular dementia (VaD) is one of the most common causes of dementia among the elderly. Despite this, the molecular basis of VaD remains poorly characterized when compared to other age-related dementias. Pervasive cerebral elevations of urea have recently been reported in several dementias; however, a similar analysis was not yet available for VaD. Methods Here, we utilized ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to measure urea levels from seven brain regions in post-mortem tissue from cases of VaD (n = 10) and controls (n = 8/9). Brain-urea measurements from our previous investigations of several dementias were also used to generate comparisons with VaD. Results Elevated urea levels ranging from 2.2- to 2.4-fold-change in VaD cases were identified in six out of the seven regions analysed, which are similar in magnitude to those observed in uremic encephalopathy. Fold-elevation of urea was highest in the basal ganglia and hippocampus (2.4-fold-change), consistent with the observation that these regions are severely affected in VaD. Discussion Taken together, these data not only describe a multiregional elevation of brain-urea levels in VaD but also imply the existence of a common urea-mediated disease mechanism that is now known to be present in at least four of the main age-related dementias.